Tannic acid-chelated zinc supplementation alleviates intestinal injury in piglets challenged by porcine epidemic diarrhea virus - Zhang, Zhengfan; Wang, Sitian; Zheng, Liyun; Hou, Yongqing; Guo, Shuangshuang; Wang, Lei; Zhu, Liangyun; Deng, Cuifang; Wu, Tao; Yi, Dan; Ding, Binying (Frontiers in Veterinary Science, 2022)
Porcine epidemic diarrhea virus (PEDV) has become challenging problems in pig industry all over the world, causing significant profit losses. Tannins and organic zinc have been shown protective effects on the intestinal dysfunction caused by endotoxins. However, there is little information on tannic acid-chelated zinc (TAZ) supplementation in the diet of newborn piglets. This study was conducted to determine the effects of TAZ on the intestinal function of piglets infected with PEDV. Thirty-two 7-day-old piglets were randomly allocated to 1 of 4 treatments in a 2 × 2 factorial design consisting of 2 diets (0 or 50 mg/kg BW TAZ) and challenge (saline or PEDV). On day 9 of the trial, 8 pigs per treatment received either sterile saline or PEDV solution at 106 TCID50 (50% tissue culture infectious dose) per pig. Pigs infected with PEDV had greater diarrhea rate and lower ADG (P < 0.05). PEDV infection decreased plasma D-xylose concentration, most antioxidative enzyme activity in plasma and intestine, as well as the small intestinal villus height (P < 0.05). Plasma diamine oxidase and blood parameters were also affected by PEDV infection. Dietary supplementation with TAZ could ameliorate the PEDV-induced changes in all measured variables (P < 0.05). Moreover, TAZ decreased the concentration of malondialdehyde in plasma, duodenum, jejunum, and colon (P < 0.05). Collectively, our results indicated that dietary TAZ could alleviate PEDV induced damage on intestinal mucosal and antioxidative capacity, and improve the absorptive function and growth in piglets. Therefore, our novel findings also suggest that TAZ, as a new feed additive for neonatal and weaning piglets, has the potential to be an alternative for ZnO.